Factors affecting rill erosion of unpaved loess roads in China. Issue 13 (29th April 2014) - Cao, Longxi; Zhang, Keli; Liang, Yin
ABSTRACT This study explores factors that affect road surface erosion in a small watershed on the Loess Plateau. Global positioning system (GPS)‐assisted field surveys and geographical information system methods were applied. The results show that road surface rills in the watershed are more easily formed on main roads, which are disturbed by intensive human activities. Secondary unpaved road networks occupied the largest road surface area and contributed 49% of the total road surface rill volumes. Spatial analysis reveals that roads near residential areas or leading to other human‐disturbed land‐use types are at high risk of soil loss. In each road segment, slope gradient, road segment length and drainage area have impacts on surface rill formation and development. Among these factors, slope gradients have been verified as a controlling factor of rill erosion intensification. Both road segment length (R = 0.83, N = 82) and drainage area (R = 0.72 for road segment and 0.76 for upslope drainage areas, N = 82) significantly influence total road surface rill volumes. The interaction variable of road segment length multiplied by slope is more closely correlated with road segment soil loss than that of the independent variables alone. Linear equations composed of slope gradient, road segment length and upslope drainage area are proposed. The new equation performs much better at predicting surface soil loss from secondary road segments compared with the previous models, which have not considered upslope drainage areas. The relationships and equations from this study will be helpful for road erosion evaluation in a small watershed of the study area. Copyright © 2014 John Wiley & Sons, Ltd.